Academic community perception of smoke-free zone implementation on campus: situation analysis at UIN Sunan Kalijaga Yogyakarta - Warsito, Gita Miranda; Fatimah, Siti; Raharja, Nia Maharani; Khusnuryani, Arifah (Journal of Community Empowerment for Health, 2025)
The Indonesian government regulates the use of tobacco products by establishing Smoke-Free Zones (SFZs), including through the Sleman Regent Regulation No. 42/2012, which mandates educational institutions to implement SFZ policies. State Islamic University (UIN) Sunan Kalijaga, located in Sleman Regency, Yogyakarta, is expected to comply with this regulation, especially given its Strategic Plan to establish a Health Faculty and its broader commitment to creating a healthy campus. However, smoking remains prevalent on campus. This study aimed to analyze the perceptions, attitudes, and behaviors of the university’s academic community toward the SFZ policy as a basis for policy development. Data were collected from 1,228 respondents, consisting of 1,164 students and 64 staff (including lecturers), using a self-administered questionnaire. The survey was distributed in January 2024 and promoted through official channels and peer networks to increase the response rate. The data were analyzed using a descriptive approach, with results presented in frequencies and percentages. Findings show that, in general, respondents expressed positive support for the adoption of a campus-wide smoke-free or comprehensive tobacco-free policy.